Low‐affinity but high‐avidity interactions may offer an explanation for IgE‐mediated allergen cross‐reactivity. Issue 8 (28th May 2021) - Chang, Xinyue; Zha, Lisha; Wallimann, Alexandra; Mohsen, Mona O.; Krenger, Pascal; Liu, Xuelan; Vogel, Monique; Bachmann, Martin F.
Abstract: Background: Allergy is a global disease with overall frequencies of >20%. Symptoms vary from irritating local itching to life‐threatening systemic anaphylaxis. Even though allergies are allergen‐specific, there is a wide range of cross‐reactivities (eg apple and latex) that remain largely unexplained. Given the abilities of low‐affinity IgG antibodies to inhibit mast cells activation, here we elucidate the minimal affinity of IgE antibodies to induce type I hypersensitivity. Methods: Three mature (high‐affinity) IgE antibodies recognizing three distinct epitopes on Fel d 1, the major cat allergen, were back‐mutated to germline conformation, resulting in binding to Fel d 1 with low affinity. The ability of these IgE antibodies to activate mast cells in vitro and in vivo was tested. Results: We demonstrate that affinities as low as 10 −7 M are sufficient to activate mast cells in vitro and drive allergic reactions in vivo . Low‐affinity IgE antibodies are able to do so, since they bind allergens bivalently on the surface of mast cells, leading to high‐avidity interactions. Conclusions: These results suggest that the underlying mechanism of allergen cross‐reactivity may be low‐affinity but high‐avidity binding between IgE antibodies and cross‐reactive allergen. Abstract : Germline IgE antibodies were of low affinity to allergen. Low‐affinity IgE antibodies are able to activate mast cells in vitro and in vivo via high‐avidity binding. Allergen A induces specific high‐affinity IgE antibodies, but with low affinity to allergen B, which could activate mast cells by high‐avidity binding to IgE antibodies. Abbreviations: OD595, optical density 595 nm; PBS, phosphate‐buffered saline.